Дистанційна освіта в Україні – реалії вищої школи - Карамушка, Олександр; Karamushka, Olexandr; Крикун, Аліна; Krikun, Alína; Осадчий, Анатолій; Osadchiy, Anatoliy (Дніпровський державний аграрно-економічний університет, 2020)
Щоб зробити дистанційне навчання максимально ефективним, воно має бути належним чином утворено через систему організації, технології, програмування та програмних кроків. Платформа дистанційного навчання є ключовим компонентом комунікації партнерів з дистанційної освіти.To make distance learning as effective as possible, it has be properly formed through a system of organization, technology, programming and program steps. There is a distance learning platform a key component of communication for distance education partners.To make distance learning as effective as possible, it has be properly formed through a system of organization, technology, programming and program steps. There is a distance learning platform a key component of communication for distance education partners.
Distance education in Ukraine - the realities of higher education
Keywords: інформатизація освіти; Informatization of education; дистанційне навчання; distance learning; системне обслуговування; system maintenance